Effectiveness of anti-IL-5/5Rα biologics in severe asthma in real-world studies: a systematic review and meta-analysis - Christos Kyriakopoulos; Efthymia Papadopoulou; Dimitrios Potonos; Konstantinos Exarchos; Evangelos Beris; Christina Aggelopoulou; Stavros Tryfon; Athena Gogali; Konstantinos Kostikas (ERJ Open Research)
Background Three biologics targeting interleukin 5 (anti-IL-5) or its receptor-α (anti-IL-5Rα) are approved for patients with severe asthma. Methods We systematically searched the literature published in Medline and Embase up to 1 May 2023 to identify observational studies and nonrandomised trials that assess the response to anti-IL-5/5Rα in real-life patients with severe eosinophilic asthma. We also performed random-effects meta-analyses. Results We identified 6401 studies, of which 92 with 9546 patients were analysed. Biologics use was associated with a 62% reduction in severe exacerbations (risk ratio 0.38, 95% CI 0.29–0.50) and a 54% reduction in hospitalisations (risk ratio 0.46, 95% CI 0.35–0.61) at 12 months of treatment, compared to pre-treatment. Biologics improved asthma control (decrease in asthma control questionnaire score by 1.11 points (95% CI −1.29–−0.94) and increase in asthma control test score by 6.41 points (95% CI 5.66–7.16)) and increased the asthma quality of life questionnaire score by 1.08 points (95% CI 0.88–1.28) and forced expiratory volume in 1 s by 0.21 L (95% CI 0.15–0.27) at 12 months. There was a significant reduction in oral corticosteroids use of 51% (risk ratio 0.49, 95% CI 0.42–0.56), with a mean dose reduction of 6.01 mg·day−1 (95% CI −7.55–−4.48) at 12 months of treatment. Similar findings were observed at 3–4, 6 and 24 months. A biomarker-related response to treatment was also noted. Conclusions This comprehensive meta-analysis summarises the significant clinical response to anti-IL-5/5Rα biologics in real-life studies, providing important insights for their use in clinical practice.